An Evaluation of Finding Aid Accessibility for Screen Readers. - Southwell, Kristina L.; Slater, Jacquelyn (Information Technology & Libraries, 2013)
Since the passage of the American Disabilities Act in 1990 and the coincident growth of the Internet, academic libraries have worked to provide electronic resources and services that are accessible to all patrons. Special collections are increasingly being added to these web-based library resources, and they must meet the same accessibility standards. The recent popularity surge of Web 2.0 technology, social media sites, and mobile devices has brought greater awareness about the challenges faced by those who use assistive technology for visual disabilities. This study examines the screen-reader accessibility of online special collections finding aids at 68 public US colleges and universities in the Association of Research Libraries.